An Analysis of Illocutionary Act Made by the Main Character of Super 8 Movie and Its Application in Teaching Speaking to Eleventh Grade Students of Senior High School - Resti Amalia (Scripta : English Department Journal, 2019)
This study is aimed at finding out illocutionary act made by the main character of Super 8 movie and itsapplication in teaching speaking to eleventh grade students of senior high school. This study usesspeaking and the part descriptive research. The data collected by documentation. The primary data istaken from the Super 8 movie as the main source data. The secondary data is analyzed the spoken andgesture of main Super 8 movie. The procedure of analyzing the data begins by analyzing the types ofillocutionary acts of main character utterance’s. The researcher find there are four types ofillocutionary acts made by main character in Super 8 movie. Those are representative 28 utterances(33.7%), commisive 14 utterances (16.9%), directive 21 utterances (25.3%), expressive 20 utterances(24.1%). The application of the result, it is focused on teaching of speech materials in senior highschool.